CFD Study of the Aero@UBI03 Shell - Rodrigues, Jorge Filipe Cardoso (2021)
Over the last 35 years, Shell has organized a student programme focused on road vehicles energy optimisation called Shell Eco¬Marathon. The competition has seen over the years a lot of improvement in design choices which led to new records in energy efficiency. At UBI, a similar story has happened since its first participation in the competition in 2014. In 2019, in its third vehicle iteration, the AERO@UBI03 team won the Circular Economy Award and achieved 612 km/kW h at the main event, the 6th place in the battery electric prototype category. In this work, a full aerodynamic analysis using Computational Fluid Dynamics, with the software OpenFOAM, was performed to evaluate the flow, pressure contours, drag and lift using the k-?SST turbulence model and wall functions available in the OpenFOAM software. It was discovered that the vehicle produces a four vortices wake, two generated by the front wheels fairings and the other two by the geometry of the vehicle. It was also noticed that the stagnation point was in a not optimal position as it creates a pressure drop when the flow moves to the underside of the vehicle. The prototype has a SCD of 0.03227 m2 and a SCL of -0.03835 m2 . A few more studies were conducted by adjusting the height of the vehicle as well as the angle of attack. These showed that improvements were possible specially in the fairings design in order to reduce the existent downforce.